Temporal trend of tuberculosis incidence and its spatial distribution in Macapá - Amapá - Clóvis Luciano Giacomet; Marcio Souza Santos; Thaís Zamboni Berra; Yan Mathias Alves; Luana Seles Alves; Fernanda Bruzadelli Paulino da Costa; Antonio Carlos Vieira Ramos; Juliane de Almeida Crispim; Aline Aparecida Monroe; Ione Carvalho Pinto; Regina Célia Fiorati; Marcos Augusto Moraes Arcoverde; et al. (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To evaluate the temporal trend of tuberculosis incidence after the implementation of the rapid molecular test (RMT-TB), to identify whether tuberculosis presents seasonal variation and to classify the territory according to case density and risk areas in Macapá, Amapá. METHODS: Ecological study of tuberculosis cases registered in the Sistema de Informação de Agravos de Notificação (SINAN - Information System for Notifiable Diseases) between 2001 and 2017. We used the Prais-Winsten test to classify the temporal trend of incidence and the interrupted time series to identify changes in the temporal trend before and after the implementation of the rapid molecular test, and to verify seasonality in the municipality. The Kernel estimator was used to classify case density and scan statistics to identify areas of tuberculosis risk. RESULTS: A total of 1,730 cases were identified, with a decreasing temporal trend of tuberculosis incidence (−0.27% per month, 95%CI −0.13 to −0.41). The time series showed no change in level after the implementation of the GeneXpert®MTB/RIF molecular test; however, the incidence increased in the post-test period (+2.09% per month, 95%CI 0.92 to 3.27). Regarding the seasonal variation, it showed growth (+13.7%/month, 95%CI 4.71 to 23.87) from December to June, the rainy season - called amazon winter season -, and decrease (−9.21% per month, CI95% −1.37 to −16.63) in the other periods. We classified areas with high density of cases in the Central and Northern districts using Kernel and identified three protection clusters, SC1 (RR = 0.07), SC2 (RR = 0.23) and SC3 (RR = 0.36), and a high-risk cluster, SC4 (RR = 1.47), with the scan statistics. CONCLUSION: The temporal trend of tuberculosis incidence was decreasing in the time series; however, detection increased after the introduction of RMT-TB, and tuberculosis showed seasonal behavior. The case distribution was heterogeneous, with a tendency to concentrate in vulnerable and risk territories, evidencing a pattern of disease inequality in the territory.